Students’ intention to reduce microplastic pollution: a future solution - Zainudin, Norzalina; Ghamadzan, Nurul Alia Batrisya; Jusoh, Zuroni Md; Nordin, Nurnaddia; Nordin, Nurhaiza; Munusami, Chandramalar (Human Resources Management Academic Research Society (HRMARS), 2024)
Microplastics are a growing environmental issue, posing risks to marine life and humans. Reducing plastic pollution requires understanding consumer behavior. This study aimed to test the Theory of Reasoned Action (TRA), combined with environmental concern, in predicting students' intentions to reduce microplastic pollution. Using data from 200 university students, hierarchical regression analysis revealed that both attitude and environmental concern significantly influenced intentions to reduce pollution. However, subjective norms had no effect, suggesting that social influence from friends and family may not be as pivotal in shaping these particular environmental intentions among university students. This study highlights the effectiveness of the Theory of Reasoned Action (TRA), enhanced by the inclusion of environmental concern, in predicting university students' intentions to reduce microplastic pollution. The strong influence of both attitude and environmental concern underscores the need to prioritize these factors in strategies aimed at fostering environmentally responsible behaviors. Although subjective norms did not show a significant effect, the findings offer important insights for future research and provide practical implications for shaping environmental policies and educational initiatives.